Findings from a mixed‐methods pragmatic cluster trial evaluating the impact of ethics education interventions on residential care‐givers. Issue 2 (3rd October 2020) - Gallagher, Ann; Peacock, Matthew; Williams, Emily; Zasada, Magdalena; Cox, Anna
Abstract: There has been little previous research regarding the effectiveness of ethics education interventions for residential care‐givers. The Researching Interventions to Promote Ethics in social care project responded to the question: Which is the most effective ethics education intervention for care‐givers in residential social care? A pragmatic cluster trial explored the impact of three ethics education interventions for: (a) interactive face‐to‐face ethics teaching; (b) reflective ethics discussion groups; and (c) an immersive simulation experience. There was also a control arm (d). 144 trial participants were recruited from 39 residential care homes for older people in southern England. Change scores compared across intervention arms showed a significant reduction in work‐related moral stress in the teaching arm compared with control group ( p  = .03); there were no significant differences between control and intervention arms in change scores for moral sensitivity, interpersonal reactivity (empathy) or ethical leadership. Qualitative data themes were as follows: ethical care; care challenges; and ethical care inhibitors. Overall findings stimulate reflection on the value of three different ethics education interventions and the most appropriate means to evaluate their impact. Findings suggest the complexity and diverse nature of ethical competence in care. We suggest a way forward for research evaluating ethics education.